Insidensi dan Profil Penyakit Psoriasis di RS Martha Friska Multatuli Medan Periode Januari−Desember 2022 - Viktoria Thanita (MEDICINUS, 2023)
Background: Psoriasis is a chronic, recurrent, inherited immunologic disorder. Psoriasis is characterized by changes in epidermal cell growth and differentiation. The mechanism of skin inflammation involves the activation of cytokines, chemokines, and growth factors that results in impaired regulation of keratinocytes, inflammatory cells, and blood vessels. This study aimed to evaluate incidence and profile of psoriasis patients at Martha Friska Multatuli Hospital, Medan, in January-December 2022. Method: This is a descriptive study using retrospective, cross-sectional design, where data collection is carried out from the medical record data of Martha Friska Multatuli Hospital. Results: Most of psoriasis cases (42 cases; 65.63%) in Martha Friska Multatuli Hospital is existing patients. Psoriasis was reported to be more prevalent in women (33 cases; 51.57%). Based on body mass index (BMI), psoriasis was found the most in those whose BMI <24,9 (34 case; 53.14%). Based on age, psoriasis was found the most in elderly (>60 years) with 26 cases (40.64%).